Exploring the Interplay of Positive Psychological Capital and Career Adaptability in Multinational Corporations - Anwar, Rana Salman; Krivokapic, Ranka; Androniceanu, Armenia; Ahmed, Rizwan Raheem (Transformations In Business & Economics, 2025)
The aim of this study is to investigate how positive psychological capital, employee resilience, career calling, and role overload interact to shape career adaptability among employees in multinational firms in Pakistan. The study investigates the impact of employee resilience as a mediator in the relationship between positive psychological capital and career flexibility, as well as the moderating effects of career calling and role overload. Design/methodology/approach: The study used a cross-sectional design, and data were obtained from 287 employees of multinational firms in Pakistan. Positive psychological capital, employee resilience, professional calling, job overload, and career adaptability were all assessed using self-report questionnaires. PLS-SEM (Partial Least Squares Structural Equation Modelling) was used to examine the data. Findings: The findings demonstrated that positive psychological capital has a substantial influence on job adaptability as well as community and individual employees’ resilience. Furthermore, resilience influenced the association between good psychological capital and job adaptability considerably. The connection between positive psychological capital and career flexibility was considerably reduced by career calling, while role overload had a modest moderating effect. Originality: This study adds to the body of knowledge by providing empirical evidence of the complex relationships between positive psychological variables, employee resilience, and career adaptability. The study expands on positive psychology in the context of careers, emphasising the importance of psychological resources and contextual elements in supporting individuals’ adaptive behaviours and well-being in their careers.
Keywords: positive psychological capital; employee resilience; career calling; role overload; career adaptability